ROLE AND KNOWLEDGE OF THE HUSBAND IN ACCOMPANYING THE WIFE BY ATTENDING THE PRENATAL GENTLE YOGA CLASS - Anggrawati Wulandari; Retno Palupi Yonni Siwi; Ridatul Nafsiyah (Jurnal SMART Keperawatan, 2024)
Many pregnant women do not take prenatal gentle yoga classes because their husband’s roles and knowledge.The aim of this research is to analyze the relationship between the role and knowledge of husbands accompanying their wives by attending prenatal gentle yoga classes.The design this research is observational analytics with a cross sectional approach,sample of pregnant women, total of 30 respondents.Sampling used purposive sampling technique.Data collection uses a questionnaire adopted from previousresearch.Data analysis used the Chi square statistical test.The research results, most of the husband's role in prenatal yoga wassupported by 16 people (53.4%),almost half of the respondents had insufficient knowledge 11 people (36.7%),and the majority did not take prenatal yoga classes 18 people (60.0%).The results of the Chi square statistical test have P value < α 0.05 (0.000), there is arelationship between the role of the husband accompanying his wife and attending prenatal gentle yoga classes,and the P value < α0.05 (0.001) is obtaine,meaning there is a relationship between knowledge and attending prenatal gentle yoga classesThe pregnantwomen's participation in prenatal yoga classes is influenced by their husband's role and knowledge.It is hoped that pregnant women will be motivated to regularly attend prenatal yoga classes.